Military Expenditure, Governance, and Environmental Degradation in Sub-Saharan Africa - Simplice Asongu; Cheikh T. Ndour (African Governance and Development Institute (AGDI), 2023)
This article examines how good governance counteracts the effects of military expenditure on carbon emissions in forty African countries. The Generalized Method of Moments (GMM) is used to analyze time series data from 2010-2020. Military expenditure per capita is used to measure military expenditure per penetration, while CO2 emissions per capita are used as an indicator of environmental degradation. The following findings are established. First, from the non-interactive regressions, we find suggestive evidence that arms expenditure increases CO2 emissions. All indicators of good governance contribute to the increase of CO2 emissions. Second, with interactive regressions, we find that improved governance has a negative effect on CO2 emissions per capita. Third, the results are robust to a sensitivity check, considering the synergy effects of governance. This paper provides policy recommendations on low-carbon economies, military expenditure and governance that could help to ensure environmental sustainability by reducing CO2 emissions. In addition, the study findings can provide guidance to other developing countries seeking to implement effective approaches to environmental sustainability while strengthening climate change mitigation and adaptation measures.
Keywords: 330; climate change; Emission reduction; Environmental degradation; Sustainability; Econometric analysis